The Model of Purchasing Decisions Making For Honey Product - Agus Mulyana; Deden Komar Priatna; Anne Lasminingrat; Dodi Sukmayana; Dodi Tisna Amijaya; Luthfi Setiadiwibawa; Rudi Suprianto Ahmadi (Journal of Accounting and Finance Management, 2023)
This study aims to explore the perception of Perhutani brand honey products' attributes, brand image, and their influence on consumer purchasing decisions. To achieve this, both descriptive and explanatory survey methods were utilized to understand the behavior of variables and test hypotheses. The research type adopted was causality-based, focusing on establishing a causal relationship between product attributes, brand image, and buying decisions. Individual analysis was conducted on consumers of Perhutani brand HONEY at Ahmad Yani and Setiabudi outlets in Bandung. With a cross-sectional approach, this research collected empirical data to gauge the majority population's opinion. The study found that product performance attributes and reference groups have a considerable impact on the products' selling price trend. The product mix performance and the influence of reference groups play a crucial role in shaping brand image. They also significantly impact purchase decisions. Interestingly, the relationship between brand image and the selling price trend is closely linked. Similarly, the performance of the product mix is also dependent on the reference group.